2017
DOI: 10.3847/1538-4357/aa862d
|View full text |Cite|
|
Sign up to set email alerts
|

Meterwavelength Single-pulse Polarimetric Emission Survey. III. The Phenomenon of Nulling in Pulsars

Abstract: A detailed analysis of nulling was conducted for the pulsars studied in the Meterwavelength Single-pulse Polarimetric Emission Survey. We characterized nulling in 36 pulsars including 17 pulsars where the phenomena were reported for the first time. The most dominant nulls lasted for a short duration, less than five periods. The longer duration nulls extending to hundreds of periods were also seen in some cases. A careful analysis showed the presence of periodicities in the transition from the null to the burst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
122
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(135 citation statements)
references
References 62 publications
(97 reference statements)
12
122
0
1
Order By: Relevance
“…Another similar phenomenon is periodic nulling that has been widely reported in many pulsars (Herfindal & Rankin 2007, 2009Rankin & Wright 2008;Rankin et al 2013;Gajjar et al 2014Gajjar et al , 2017Basu et al 2017). The periodicities of the amplitude modulation are very similar to periodic nulling, causing Basu et al (2017) to propose that they both may have a common origin. Herfindal & Rankin (2007) used the rotating subbeam carousel model to account for periodic nulling, in which the conal subbeams rotate around the central core component.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Another similar phenomenon is periodic nulling that has been widely reported in many pulsars (Herfindal & Rankin 2007, 2009Rankin & Wright 2008;Rankin et al 2013;Gajjar et al 2014Gajjar et al , 2017Basu et al 2017). The periodicities of the amplitude modulation are very similar to periodic nulling, causing Basu et al (2017) to propose that they both may have a common origin. Herfindal & Rankin (2007) used the rotating subbeam carousel model to account for periodic nulling, in which the conal subbeams rotate around the central core component.…”
Section: Discussionsupporting
confidence: 53%
“…When the line of sight passes through the empty region between two conal subbeams or through a extinguished subbeam, nulling occurs, and this can repeat after certain spin periods of the pulsar. However, Basu et al (2017) found that the missing line of sight model did not adequately explain the periodic nulling observed in many pulsars, particularly in pulsars with core components. Additionally, because of lack of phase memory and partial nulls, the missing line of sight model is probably not applicable to the quasi-periodic feature seen in PSR J1741−0840 (Gajjar et al 2017).…”
Section: Discussionmentioning
confidence: 91%
“…Contrasting behaviour of drifting and other periodic modulations are clearly illustrated in pulsars where both effects are seen in pulse sequence (Basu et al 2017(Basu et al , 2019a. In all such cases the low frequency feature in fluctuation spectra can be identified as periodic modulation.…”
Section: Other Periodic Modulationsmentioning
confidence: 92%
“…There are also examples of quasi-periodic variations in intensity in the form of periodic amplitude modulation and periodic nulling. In a series of studies Basu et al (2016Basu et al ( , 2017; Mitra & Rankin (2017); Basu & Mitra (2018b); Basu et al (2019a,b) have identified and delineated the properties of these phenomena whose physical properties were clearly different from subpulse drifting. 1 In order to explain mode changes, one needs to appeal to a mechanism which causes the radio emission to change rapidly, and subsequently exhibit stable radio emission with different modal characteristics.…”
Section: Introductionmentioning
confidence: 99%